- IMPLEMENTASI STRATEGI SISTEM PENJAMINAN MUTU PADA PENDIDIKAN NON FORMAL: - - Kholisotul Ula, Naila; Zainabiyyi, Syafiqoh Zuhda Samiyah (UHN IGB Sugriwa Denpasar, 2024)
The existence of quality assurance in education is highly necessary in this regard. In this context, Government Regulation No. 19 of 2005, Chapter XV, Article 91, Paragraph 1, states that quality assurance is mandatory at all levels of education, both formal and non-formal. In collecting data, this research employs a literature study method. Thus, the data obtained can come from journals, articles, magazines, books, and other reading sources. To strengthen and provide an overview of the research theme being carried out, the researcher added previous studies related to the implementation of non-formal education in various major cities in Indonesia. In this discussion, the researcher seeks to reveal the essence of the existence of quality assurance, non-formal education units, quality assurance strategies for non-formal education, and the impact of quality assurance in non-formal education. Therefore, with this research, the focus of various parties on the existence of non-formal education in Indonesia can be increased. With these efforts, the condition of education in Indonesia is highly likely to experience an improvement in quality. This is based on the increased access to education available to Indonesian citizens.